Modeling and simulation of logistics flows 2 - Réveillac, Jean-Miche (ISTE Ltd/John Wiley and Sons Inc, 2017)
Volume 2 begins with an introduction and 4 chapters implementing software tools on cases of practical applications and it ends with a conclusion: The various tools used in this volume. Operational research with a spreadsheet. Dashboards with spreadsheets and pivot tables. Scheduling and planning with a project manager. The traffic simulation. The conclusion shows the new features that are expected to emerge on spreadsheets as well as project managers, developments and convergences between traffic simulators and new infrastructure that are emerging on road networks. Annex 1 focuses on the installation Solver in Microsoft Excel and Annex 2 focuses on the installation of the Java Development Kit.